1993
DOI: 10.1099/0022-1317-74-4-699
|View full text |Cite
|
Sign up to set email alerts
|

The role of gp55 N-glycosylation in pathogenesis of Friend spleen focus-forming virus

Abstract: The product of the envelope gene (gp55) of Friend spleen focus-forming virus is responsible for the acute form of erythroleukaemia caused by this virus. In order to investigate the role that the four known N-linked carbohydrate side-chains of gp55 play in pathogenesis, we have inactivated the four N-glycosylation signals by mutating the asparagine residues of these four sites into serine. When glycosylation sites 1 and/or 2 were altered, the viruses remained fully pathogenic. However, mutation at either of gly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1994
1994
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…Previous studies have shown that gp55 homodimerization and glycosylation are required for gp55 to be efficiently translocated to the cell surface (29,49,50) and that this translocation is required for pathogenesis. Our data demonstrate that Sf-Stk localizes primarily in the cytosol and that plasma membrane localization is enhanced through its association with gp55.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that gp55 homodimerization and glycosylation are required for gp55 to be efficiently translocated to the cell surface (29,49,50) and that this translocation is required for pathogenesis. Our data demonstrate that Sf-Stk localizes primarily in the cytosol and that plasma membrane localization is enhanced through its association with gp55.…”
Section: Discussionmentioning
confidence: 99%
“…Only a small fraction of F-SFFVp gp55 molecules is processed in the Golgi apparatus, yielding a second glycoform of this protein, gp65, which carries complex type N-glycans as well as partially sialylated O-linked sugar chains [30,311 and can readily be detected on the cell surface. Since mitogenic activation of EpoR by the F-SFFVp env product is assumed to require the interaction of the two proteins at the cell surface, plasma membrane expression of gp65 is considered to be a prerequisite for the leukemogenicity of Mutational analyses, in which either single or combinations of different glycosylation sites of F-SFFVp Env were inactivated [32], revealed that the viruses remained fully pathogenic when the N-terminal glycosylation sites 1 and/or 2 were mutated. Elimination of glycosylation sites 3 and 4, located in the C-terminal part of the molecule, however, rendered the virus apathogenic, independent of mutations at other sites.…”
Section: Friend Murine Leukemia Virus Complexmentioning
confidence: 99%